Spectral properties and geology of bright and dark material on dwarf planet Ceres. (22nd January 2018) - Thangjam, G.; Nathues, A.; Platz, T.; Hoffmann, M.; Cloutis, E. A.; Mengel, K.; Izawa, M. R. M.; Applin, D. M.
Abstract: Variations and spatial distributions of bright and dark material on dwarf planet Ceres play a key role in understanding the processes that have led to its present surface composition. We define limits for "bright" and "dark" material in order to distinguish them consistently, based on the reflectance of the average surface using Dawn Framing Camera data. A systematic classification of four types of bright material is presented based on their spectral properties, composition, spatial distribution, and association with specific geomorphological features. We found obvious correlations of reflectance with spectral shape (slopes) and age; however, this is not unique throughout the bright spots. Although impact features show generally more extreme reflectance variations, several areas can only be understood in terms of inhomogeneous distribution of composition as inferred from Dawn Visible and Infrared Spectrometer data. Additional material with anomalous composition and spectral properties are rare. The identification of the composition and origin of the dark, particularly the darkest material, remains to be explored. The spectral properties and the morphology of the dark sites suggest an endogenic origin, but it is not clear whether they are more or less primitive surficial exposures or excavated subsurface but localized material. The reflectance, spectral properties, inferred composition, and geologic context collectively suggest that the bright and dark material tends to gradually change toward the average surface over time. This could be because of multiple processes, i.e., impact gardening/space weathering, and lateral mixing, including thermal and aqueous alteration, accompanied by changes in composition and physical properties such as grain size, surface temperature, and porosity (compaction).